Cathy Milliken - Composer, Performer, Director - Milliken, Catherine (2023)
Cathy Milliken is an international award-winning performer and composer known for her evocative instrumental and vocal works.She moves between manifold musical worlds, taking great joy in facilitating creativity and participation. The diversity and relevance of her output has won her international recognition as a leading composer, creative director, educational consultant and performer. [according to the site editor's information]